2022
DOI: 10.1002/anie.202209542
|View full text |Cite
|
Sign up to set email alerts
|

Generating High‐valent Iron‐oxo ≡FeIV=O Complexes in Neutral Microenvironments through Peroxymonosulfate Activation by Zn−Fe Layered Double Hydroxides

Abstract: The universal limit on the pH conditions is disturbing peroxymonosulfate (PMS)-triggered high-valent iron-oxo systems in environmental applications. Here, we propose for the first time the construction of a neutral microenvironment on the surface of ZnÀ Fe layered double hydroxide (ZnFe-LDH) by using the amphoteric properties of zinc hydroxide, which continuously generates �Fe IV =O over a wide pH range of 3.0-11.0 in activating PMS. The �Zn(OH) 2 moiety offers a neutral microenvironment at the phase interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…However, no DMPO-·OH and DMPO-·SO 4 – signals were observed when FePc was incorporated in CN. Instead, a set of septet peaks was recorded, which could be ascribed to the formation of 5,5-dimethyl-1-pyrrolidone-2-oxyl (DMPO-X). The formation of DMPO-X indicated that highly reactive oxygen-containing species were generated during the catalytic oxidation process, leading to the rapid oxidation of DMPO . Moreover, the highly reactive oxygen-containing species were produced by the reaction between FePc and PDS, and the combination of CN and FePc further promoted the generation of these species.…”
Section: Resultsmentioning
confidence: 99%
“…However, no DMPO-·OH and DMPO-·SO 4 – signals were observed when FePc was incorporated in CN. Instead, a set of septet peaks was recorded, which could be ascribed to the formation of 5,5-dimethyl-1-pyrrolidone-2-oxyl (DMPO-X). The formation of DMPO-X indicated that highly reactive oxygen-containing species were generated during the catalytic oxidation process, leading to the rapid oxidation of DMPO . Moreover, the highly reactive oxygen-containing species were produced by the reaction between FePc and PDS, and the combination of CN and FePc further promoted the generation of these species.…”
Section: Resultsmentioning
confidence: 99%
“…Phenylmethyl sulfoxide (PMSO) was chosen as a probe to detect the high-valent iron species in the N/C-mediated Fe­(III)/H 2 O 2 system. As shown in Figure S31, the consumption of PMSO was accelerated in the Fe­(III)/H 2 O 2 system via the assistance of N/C. However, the yield of phenylmethyl sulfone (PMSO 2 ) was not observed, indicating the decay of PMSO was radical induced and high-valent iron in the N/C-mediated Fe­(III)/H 2 O 2 system was negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has reported that Fe­(IV) is often formed in PS system activated by iron-based catalyst. , For insight into the contribution of Fe­(VI), DMSO was used as a scavenger of Fe­(VI) . The methyl phenyl sulfoxide (PMSO) can be converted to methyl phenyl sulfone (PMSO 2 ) under the attack of Fe­(IV) (eqs and ). , As the concentration of DMSO decreased 43.8%, Fe­(IV) made a certain contribution in degrading CBZ.…”
Section: Resultsmentioning
confidence: 99%